Taxonomy and phylogenetic appraisal of Leptosphaeria chatkalica sp. nov. (Leptosphaeriaceae, Pleosporales) from Uzbekistan - Lestari, Anis S.; Wanasinghe, Dhanushka N.; Gafforov, Yusufjon; Tennakoon, Danushka S.; Chethana, K. W. Thilini; Abdurazakov, Aziz; Promputtha, Itthayakorn; Hyde, Kevin D. (Phytotaxa, 2021)
Leptosphaeria chatkalica, found on dead stems of dicotyledon from Chatkal ridge of Western Tien Shan Mountains in Uzbekistan, is presented as a novel species based on morphological details and multi-locus phylogenetic analyses. Phylogenetic relationships of the novel species were established by analyzing the combined sequence data of LSU, ITS, SSU and tef1-α in Maximum parsimony, Maximum likelihood and Bayesian inference analyses. Leptosphaeria chatkalica is characterized by perithecial ascomata, club-like pedicel asci and yellowish-brown, 3-septate, fusiform ascospores with a mucilaginous sheath. A comprehensive characterization and micro-graphs, together with a comparison with other Leptosphaeria species are given.